Adult-onset leukodystrophies: a practical guide, recent treatment updates, and future directions - Muthusamy, Karthik; Sivadasan, Ajith; Dixon, Luke; Sudhakar, Sniya; Thomas, Maya; Danda, Sumita; Wszolek, Zbigniew K.; Wierenga, Klaas; Dhamija, Radhika; Gavrilova, Ralitza (Frontiers in Neurology, 2023)
Adult-onset leukodystrophies though individually rare are not uncommon. This group includes several disorders with isolated adult presentations, as well as several childhood leukodystrophies with attenuated phenotypes that present at a later age. Misdiagnoses often occur due to the clinical and radiological overlap with common acquired disorders such as infectious, immune, inflammatory, vascular, metabolic, and toxic etiologies. Increased prevalence of non-specific white matter changes in adult population poses challenges during diagnostic considerations. Clinico-radiological spectrum and molecular landscape of adult-onset leukodystrophies have not been completely elucidated at this time. Diagnostic approach is less well-standardized when compared to the childhood counterpart. Absence of family history and reduced penetrance in certain disorders frequently create a dilemma. Comprehensive evaluation and molecular confirmation when available helps in prognostication, early initiation of treatment in certain disorders, enrollment in clinical trials, and provides valuable information for the family for reproductive counseling. In this review article, we aimed to formulate an approach to adult-onset leukodystrophies that will be useful in routine practice, discuss common adult-onset leukodystrophies with usual and unusual presentations, neuroimaging findings, recent advances in treatment, acquired mimics, and provide an algorithm for comprehensive clinical, radiological, and genetic evaluation that will facilitate early diagnosis and consider active treatment options when available. A high index of suspicion, awareness of the clinico-radiological presentations, and comprehensive genetic evaluation are paramount because treatment options are available for several disorders when diagnosed early in the disease course.